Impersonal Constructions in Croatian - Zovko, Irena (1999)
Constructions involving a dative experiencer and the reflexive form of an activity verb, are fairly common in Croatian. However, in most grammars of Croatian such constructions are often neglected or written off as being impersonal or having what is usually called a logical subject. We shall try to prove that Role and Reference Grammar provides satisfactory means of explaining that such constructions are not impersonal, but involve a particular type of internal experience predicates with dative experiencers as undergoers.